Windlines. Volume 5, number 2 (January 2012) - (:unkn) unknown (American Organ Institute, 2012)
Issue of the American Organ Institute newsletter; advertisement for concert by Ken Double and Skip Stine; "Principal Chorus" update announcing the creation of the American Theatre Organ Library at AOI based on the ATOS archives, congratulating students for excellence in academics and competitions, and thanking AOI supporters; "First Impressions" column by student James Richardson; AOI events; "Engagements" section listing Dr. Schwandt's appearances in the area during the semester.
Keywords: American Organ Institute; Organ music -- Study and teaching -- Oklahoma -- Norman; Organ (Musical instrument) -- Conservation and restoration